Biodiversity and notes on carabid beetles from Angola with description of new taxa (Coleoptera: Carabidae) - Serrano, Artur R. M.; Capela, Rúben A.; Santos, Carmen Van-Dúnem Neto (Zootaxa, 2017)
An annotated list of species of carabids sampled in Angola during three entomological trips is presented. A total of 111 species/subspecies were identified and some ecological remarks as well as its known distribution in this country are provided. Perigona liboloensis sp. n., Lasiocera schuelei sp. n. and Galerita procera capelai ssp. n., are described. New records of some genera and species previously unknown from Angola are given. Further, two dichotomic keys are made available for the identification of Perigona (s. str.) species of Africa and Lasiocera species of southern Africa, respectively.